References for the integration of vocal performance and the scenographic creation of the Iraqi theatrical show [Baghdad, the eternal between seriousness and humor] as a model (Journal of the College of Basic Education, 2022)
The theater has witnessed throughout its long history; Lots of changes that involved my structure ( text- Width ) ; These changes were based on multiple shifting references; affected the appearancemany literary or directing trends; The current research is an attempt to trace the referencesAdopted by the scenographic construction as a projection vessel + vocal performance as a standThe language of the text in the Iraqi theatrical show; Adapted from the play (Baghdad Al-Azl Bain Al-Jedd).and humor) is a model for him. The study came in four chapters; The first of which dealt with the research methodologyThe second is a brief discussion of the most important references for scenographic composition and vocal performanceThrough the different stages and trends, and fixing the most prominent indicators that the researchers concluded